A educação jurídica num mundo globalizado : o sentido de criar sentidos - Macedo Júnior, Ronaldo Porto (2014)
I believe the challenges imposed on legal education by globalization are multiple. To take on these challenges it is necessary to understand their significance and how they impact the law and the world, and how their involvement affects the life of a professional in the field of law. To understand globalization is a task that requires an interdisciplinary education in economics, politics, and institutional ethics at both the national and international levels. It is important to note as well that the function of law schools should not be limited to preparing their students professionally and technologically in order to carry out their jobs in the market place. Besides this, students should be trained to reflect on the essence of law itself and the development of life in the field of law within a global world. This point has not been addressed by law schools themselves which claim to be modern and on the cutting edge. If the field of legal education hopes to avoid the vices of conservatism, it is vital to know how to preserve lessons learned from the past, and most specifically, to reflect on its purpose for those who are its target group.